An Efficient Approach Towards Total Synthesis of Retinoid Compounds - Kumar, Bimal; Pandey, Satyendra Kumar (My University, 2017)
Due to the biological importance of retinoids in neural processes, embryonic development, cell differentiation, proliferation activities, uses as chemotherapeutic drugs and dermatological diseases; we worked on a concise and highly efficient synthetic approach for the synthesis of (E)-5-(2-(3,5,5,8,8-pentamethyl-5,6,7,8-tetrahydronaphthalen-2-yl)prop-1-en-1-yl)thiophene-2-carboxylic acid. A series of coupling reaction conditions were explored for the Heck Coupling reaction to form required acid and its methyl ester derivative. Column Chromatography, 1H-NMR, 13C-NMR and FTIR techniques were employed to purify and confirm the formation of compounds using different reaction paths.
Keywords: Retinoid Compounds; R x R agonists; Tgase activity in Leukemia Cell; Heck Coupling Reaction; Chemotherapeutic Drug